WORLD OF THE UKRAINIAN WRITING IN RESEPTION OF MYKOLA ZHULYNSKY Mykola Zhulynsky. Ukrainian literature: creators and works: to the students, university entrants, students, teachers. – C.: Lybid’, 2011. – 1152 s. - Dmytrenko , M. K. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In a review the looks of scientist of specialist in folk-lore and writer on a new labor of Mykola Zhulynsky are given «Ukrainian literature: creators and works: to the students, university entrants, students, teachers».